Diet consistency but large-scale isotopic variations in a deep-sea shark: The case of the velvet belly lantern shark, Etmopterus spinax, in the northeastern Atlantic region and Mediterranean Sea. (April 2022) - Besnard, Lucien; Duchatelet, Laurent; Bird, Christopher S.; Le Croizier, Gaël; Michel, Loïc; Pinte, Nicolas; Lepoint, Gilles; Schaal, Gauthier; Vieira, Rui P.; Gonçalves, Jorge M.S.; Martin, Ulrich; Mallefet, Jérôme
Abstract: Deep-sea elasmobranchs are commonly reported as bycatch of deep-sea fisheries and their subsequent loss has been highlighted as a long-running concern to the ecosystem ecological functioning. To understand the possible consequences of their removal, information on basic ecological traits, such as diet and foraging strategies, is needed. Such aspects have been widely studied through stomach content analysis but the lack of long-term dietary information requires other tools to be used such as stable isotopes. This study examines nitrogen and carbon isotope compositions of the velvet belly lantern shark, Etmopterus spinax, one of the most impacted shark species in northeastern Atlantic fisheries as a result of accidental catches. E. spinax was sampled at four different locations, characterized by contrasting oceanographic and ecological conditions: the western Mediterranean Sea (near the Balearic Islands), the southern Iberian upwelling system, Rockall Trough and southwestern Norwegian fjords. Stomach content analysis revealed similar prey species among sites, with a diet dominated by Euphausiacea (mostly Meganyctiphanes norvegica ) and an ontogenetic shift towards small teleost fishes, cephalopods or other crustaceans. Despite these similarities, muscle stable isotope compositions differed across sampled locations. Rather than clear dietary differences, the contrasted isotopic values are likely to reflect differences in environmental settings and biogeochemical processes affecting nutrient dynamics at the base of the food webs. Highlights: E. spinax were sampled across the northeastern Atlantic and Mediterranean Sea. Stomach contents suggested a similar diet. E. spinax fed mainly on Euphausiacea with an ontogenetic diet shift. Muscle carbon and nitrogen isotope compositions differed between locations. Isotopic differences probably resulted from mechanisms affecting the baselines.